"Lublin Triangle": Prospects for the Formation of a Transport and Logistics Cluster (Aspects of Modern Marketing Management) - Chebotarov, Ie. (Економічний вісник Донбасу, 2021)
The generalizing analysis of modern pan-European disintegration tendencies, especially against the background of forecasted such new tendencies, necessitates the search for other determinants of reliable international cooperation and the formation of stable international organizations. The new Lublin Triangle platform, consisting of Poland, Lithuania and Ukraine, which was founded in 2020, could be one of the few international organizations. The greatest economic effect and a number of concomitant institutional advantages of cooperation between these countries can give in the transport and logistics sphere with the formation of the transport and logistics cluster "Lublin Triangle". Taking into account a number of institutional and technical-functional factors, Latvia and Estonia can also be full participants in the proposed cluster; in this case, the proposed cluster may be called, for example, the Baltic-Eastern European Transport and Logistics Cluster. The categorical definition of the definition of "transport and logistics cluster" is substantiated. It is a set of spatially defined entities of all types of transport, infrastructure of their modes of transport and engineering industries, as well as related enterprises, institutions and governing bodies, which operates on the basis of a network of hubs. . The innovative nature of the proposal is that in contrast to the existing approaches in domestic and foreign science, according to which transport and logistics clusters are considered only within certain regions of a country, in this case: the understanding of the cluster , provisions and procedures of the Trans-European Transport Network (TEN-T) policy on the basis of modern marketing management; the cluster itself is offered in the form of appropriate transport and logistics hubs. The article, in addition to identifying the definition of "transport and logistics cluster" highlights the parameters of the proposed cluster with the disclosure of their content; cluster functions are classified; the structure of the network of geographical location of hubs is given. Узагальнюючий аналіз сучасних загальноєвропейських дезінтеграційних тенденцій, тим більше – на тлі прогнозованих такого роду нових тенденцій, зумовлює необхідність пошуку інших детермінант надійної міжнародної співпраці та формування стійких міжнародних організацій. Однією з таких небагатьох міжнародних організацій може стати нова платформа «Люблінський трикутник» у складі Польщі, Литви та України, яку було засновано у 2020 році. Найбільший економічний ефект і низку супутніх інституційних переваг співпраця цих країн може дати у транспортно-логістичній сфері з формуванням транспортно-логістичного кластеру «Люблінський трикутник». З урахуванням низки інституціональних
і техніко-функціональних чинників учасниками пропонованого кластеру у повному обсязі можуть бути також Латвія та Естонія; у такому разі пропонований кластер може отримати назву, наприклад Балтийсько-Східно-Європейський транспортно-логістичний кластер. Обґрунтовано категоріальне визначення дефініції «транспортно-логістичний кластер».
Це упорядкована на підґрунті мережі хабів сукупність просторово визначених суб’єктів господарювання всіх видів транспорту, інфраструктури їх шляхів сполучення та галузей машинобудування, а також споріднених з ними підприємств, установ й органів управління, яка функціонує на договірних відносинах і забезпечує їхню горизонтальну та вертикальну взаємодію. Інноваційний характер висунутої пропозиції полягає у тому, що на відміну від наявних у вітчизняній і зарубіжній науці підходів, згідно з якими транспортно-логістичні кластери розглядаються лише в межах певних регіонів окремої країни, у даному випадку: розуміння кластера виноситься на міждержавний рівень у контексті реалізації норм, положень і процедур Trans-European Transport Network (TEN-T) політики на засадах сучасного маркетинг-менеджменту; сам кластер пропонується у вигляді відповідних транспортно-логістичних хабів. У статті, окрім ідентифікації дефініції «транспортно-логістичний кластер», виокремлено параметри пропонованого кластеру з розкриттям їх змісту; класифіковано функції кластеру; надано структуру мережі географічного розміщення хабів. Обобщающий анализ современных общеевропейских дезинтеграционных тенденций, тем более на фоне прогнозируемых такого рода новых тенденций, обусловливает необходимость поиска других детерминант надежного международного сотрудничества и формирования устойчивых международных организаций. Одной из немногих международных организаций может стать новая платформа «Люблинский треугольник» в составе Польши, Литвы и Украины, основанная в 2020 году. Наибольший экономический эффект и ряд сопутствующих институциональных преимуществ сотрудничество этих стран может оказать в транспортно-логистической сфере с формированием транспортно-логистического кластера «Люблинский треугольник». С учетом ряда институциональных и технико-функциональных факторов участниками предлагаемого кластера в полном объеме могут быть также Латвия и Эстония; в таком случае предлагаемый кластер может получить название, например, Балтийско-Восточно-Европейский транспортно-логистический кластер. Обосновано категориальное определение определения «транспортно-логистический кластер». Это упорядоченная на основе сети хабов совокупность пространственно определенных субъектов хозяйствования всех видов транспорта, инфраструктуры их путей сообщения и отраслей машиностроения, а также родственных им предприятий, учреждений и органов управления, которая функционирует на договорных отношениях и обеспечивает их горизонтальное и вертикальное взаимодействие. Инновационный характер выдвинутого предложения заключается в том, что в отличие от имеющихся в отечественной и зарубежной науке подходов, согласно которым транспортно-логистические кластеры рассматриваются только в пределах определенных регионов отдельной страны, в данном случае понимание кластера выносится на межгосударственный уровень в контексте реализации норм, положений и процедур Trans-European Transport Network (TEN-T) политики на основе современного маркетинг-менеджмента; сам кластер предлагается посредством соответствующих транспортно-логистических хабов. В статье, кроме идентификации определения «транспортно-логистический кластер», выделены параметры предлагаемого кластера с раскрытием их содержания; классифицированы функции кластера; предоставлена структура сети географического размещения хабов.